2003
DOI: 10.1182/blood-2003-01-0019
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression and release of ligands for the activating immunoreceptor NKG2D in leukemia

Abstract: NKG2D ligands (NKG2DLs) mark malignant cells for recognition by natural killer (NK) cells and cytotoxic T lymphocytes via the activating immunoreceptor NKG2D. This led to the hypothesis that NKG2DLs play a critical role in tumor immune surveillance. The human NKG2DLs MICA and MICB are expressed on tumors of epithelial origin in vivo. For the other recently described set of human NKG2DLs, the UL16-binding proteins (ULBPs), expression in vivo is as yet undefined. In this study we investigated expression and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
504
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 482 publications
(519 citation statements)
references
References 32 publications
8
504
1
6
Order By: Relevance
“…Recent works have shown the remarkable role of ULBP2 as a marker for disease progression [8,21]. In addition, it has been reported that proteasome inhibitor treatment leads to a higher sensitivity to NK-cell-mediated killing by upregulation of ULBP2 expression [22], supporting its potential relevance in the development of anticancer therapy.…”
Section: Nkg2d and Nkg2a Ligation Rescues Impaired Migrationmentioning
confidence: 96%
See 2 more Smart Citations
“…Recent works have shown the remarkable role of ULBP2 as a marker for disease progression [8,21]. In addition, it has been reported that proteasome inhibitor treatment leads to a higher sensitivity to NK-cell-mediated killing by upregulation of ULBP2 expression [22], supporting its potential relevance in the development of anticancer therapy.…”
Section: Nkg2d and Nkg2a Ligation Rescues Impaired Migrationmentioning
confidence: 96%
“…This effect was abrogated by costimulation of the NKG2A receptor, while the activation of this receptor alone did not affect cell migration. These results are in keeping with the study of Culley et al [20], which describes that activating signals in NK cells, such as interaction of NKG2D with MICA promotes a stop signal to form the IS, while inhibitory signals may reverse this effect.Recent works have shown the remarkable role of ULBP2 as a marker for disease progression [8,21]. In addition, it has been reported that proteasome inhibitor treatment leads to a higher sensitivity to NK-cell-mediated killing by upregulation of ULBP2 expression [22], supporting its potential relevance in the development of anticancer therapy.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…For more than a decade, however, an impaired NK cell cytotoxic capacity in AML patients is acknowledged. [17][18][19][20][21][22] NK-cellmediated killing of a target cell depends on the balance between Impaired NK cell-mediated cytotoxicity AML cell shedding of NKG2D-L MIC and ULBP molecules 43,44 Reduced receptor expression and impaired NK cell-mediated cytotoxicity AML cell GITRL expression 45 Surface and soluble GITRL expression (surface expression is related to monocytic differentiation)…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%
“…40,41 AML cells themselves contribute to impaired NK cell-mediated killing by decreased or absent expression of surface ligands for various NK cell activating receptors, including NCRs and NKG2D. 27,28,42,43 Furthermore, AML cells can shed ligands for NKG2D, as demonstrated by the increased serum levels of MHC class I chain-related genes A and B (MICA/B) in AML patients compared with healthy controls. 43,44 These soluble ligands may provide a chronic systemic stimulus to NK cells resulting in reduced receptor expression and impaired NK cell-mediated cytotoxicity (Table 1).…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%